(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
The investigation on small indigenous species of fish (SIS) of Netrakona district was conducted from July 2003 to June 2004. A total number of 78 SIS belonging to 54 genera, 4 sub-families, 25 families and 10 orders was identified from the district. The most dominant family was Cyprinidae having 26 species under the order Cypriniformes. Puntius was the largest genus containing 7 species.The most abundant SIS was Mola (Amblypharyngodon mola) during the investigation period, whereas the least abundant SIS was Bacha (Eutropiichthys vacha). Seasonal variations were observed in the abundance of different SIS. Asiat. Soc. Bangladesh, Sci. 40(2): 309-317, December 2014